Determining highly-productive buckwheat varieties in the zone of Southern Forest-Steppe of Ukraine - Tryhub, O.; Liashenko, V.; Kutsenko, O.; Barabolia, O.; Korotkova, V.; Liashenko, K. (Scientific Progress & Innovations, 2022)
The article deals with the study results concerning determining highly productive buckwheat varieties according to their yield indicators and components as well as biological pro perties characteristic for agro-climatic conditions of the Southern Forest-Steppe zone of Ukraine. The investigation was made during 2020–2021 in field and laboratory conditions of Ustymivka Experimental Station of Plant Growing of the Institute of Plant Growing named after V. Ya. Yuriev, of the National Academy of Agrarian Sciences of Ukraine. The experiment was organized by the scheme of the control seed plot using the generally accepted cultivation technology. The studying of the experimental material was made according to the following indicators: yield capacity, plant productivity (the amount of grains, grain weight), the number of flower heads, their grain content and productivity. 12 modern buckwheat varieties of the Ukrainian selection were taken for the research: Ukrainka, CИН 3/02, Nadiyna, Olha, Slobozhanka, Selianochka, Yuvileina 100, Yaroslavna, Yelena, Volodar, Sofia, and Antaria. More yields were obtained in 2021, when the value of grain weight per 1 m2 was on a level of 254.7 g/m2 on the average (in 2020 it was 210.8 g/m2. During the whole period of experiments, such buckwheat varieties as Ukrainka, Olha, Yelena, and Sofia demonstrated the best productivity and yield capacity. On the average, during the years of research, Olha (58 pcs.), Yelena (69 pcs.), and Sofia (63 pcs.) buckwheat varieties turned out to be the most productive in the group. The highest level of flower heads’ grain content was fixed in Yelena (1.51 pcs.), Sofia (1.40 pcs.), and Olha (1.05 pcs.) determinant buckwheat varieties. During the study years, it has been found that buckwheat varieties formed more flower heads’ productivity in 2021 – 0.024 g than in 2020 (0.022 g). The research has shown that Yelena (0.043 g) and Sofia (0.040 g) buckwheat varieties have the largest average grain weight per flower head. Thus, Olha, Yelena, and Sofia buckwheat varieties are more adapted for cultivation in agro-climatic conditions of the Southern Forest-Steppe zone of Ukraine, which allows to obtain high yields (on a level of 20–25 hundredweight/ha).